2020
DOI: 10.4274/tjh.galenos.2020.2019.0361
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Positron Emission Tomography-Computed Tomography and Bone Marrow Biopsy in Detecting Bone Marrow Infiltration in Lymphoma Cases

Abstract: Amaç: Kemik iliği infiltrasyonu (Kİİ), lenfoma evresini, sağkalımı ve tedaviyi etkiler. Lenfoma hastalarında Kİİ' ni saptamada kemik iliği biyopsisi (KİB) ve positron emisyon tomografi-bilgisayarlı tomografi (PET/BT)' nin performanslarını değerlendirmek istedik. Gereç veYöntemler: 269 non-Hodgkin lenfoma (NHL) ve 110 hodgkin lenfoma (HL) hastası retrospektif olarak değerlendirildi. Kİİ' ni saptamada PET/BT ve KİB için duyarlılık, negatif prediktif değer (NPD) ve doğruluk hesaplandı. Bulgular: NHL olgularında K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(17 reference statements)
2
2
0
1
Order By: Relevance
“…This is consistent with the study done by Cistaro et al [28], the sensitivity of 18F-FDG PET/CT was found 96% (95% CI, 89-100%) while that of BMB was found 38% (95% CI, 20-57%). This is also consistent with the study done by Büyükşimşek et al [29], who included 110 patients with HL and found PET/CT sensitivity was 91.3% (95% CI, 71.96-98.93) compared to that of BMB which was 56.52% (95% CI, 34.49-76.81).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the study done by Cistaro et al [28], the sensitivity of 18F-FDG PET/CT was found 96% (95% CI, 89-100%) while that of BMB was found 38% (95% CI, 20-57%). This is also consistent with the study done by Büyükşimşek et al [29], who included 110 patients with HL and found PET/CT sensitivity was 91.3% (95% CI, 71.96-98.93) compared to that of BMB which was 56.52% (95% CI, 34.49-76.81).…”
Section: Discussionsupporting
confidence: 91%
“…In our retrospective study, we found that 18 F-FDG PET/CT exhibited significantly higher accuracy compared to BMB as a diagnostic modality. This observation aligns with several other studies 5 , 9 , 22 , 23 , 24 , that reported superior sensitivity of 18 F-FDG PET/CT over BMB, with only one study 25 indicating similar accuracy between the two diagnostic methods.…”
Section: Discussionsupporting
confidence: 91%
“…This systematic review involved some limitations. In some studies PET/CT images were interpreted using qualitative criteria [15][16][17]19,20,22,26,29,31,[34][35][36][37][38][39]42,43,47,48,50,[52][53][54], whereas in other studies both qualitative and quantitative criteria were used [18,21,[23][24][25]27,28,30,32,33,40,41,[44][45][46]49,51,55]. As the qualitative evaluation is based on a subject's experience, this might underestimate the PET/CT diagnostic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Patient selection was assessed with an unclear risk of bias in 20 of the included studies because the participants sample was unclearly defined as to whether selection was random or consecutive. For the index test, only one of the included studies [26] were assessed with an unclear risk of bias, due to insufficient reporting of results of the index test if they were interpreted with or without a knowledge of reference standard findings. In the reference standard domain, four studies had an unclear risk of bias because of poorly reporting if the reference standard were interpreted without knowledge about the index test findings.…”
Section: Methodological Quality Assesmentmentioning
confidence: 99%